Agreement between the United Kingdom of Great Britain and Northern Ireland and the Kingdom of Spain on the Participation in Certain Elections of Nationals of Each Country Resident in the Territory of the Other, Madrid, 21 January 2019. ([2023-03-22]) - Unknown
No abstract available